Momentary discomfort of high-speed trains passing through complex terrain sections under strong wind conditions. Issue 9 (1st September 2020) - Liu, Dongrun; Zhou, Wei; Zhang, Lei; Wang, Qianxuan; Zhong, Mu; Lu, Zhaijun
Abstract : Momentary discomfort caused by high-speed trains passing through complex terrain sections under strong wind conditions has become an urgent engineering problem in China. However, few scholars or research institutions have focused on this topic, and there are no standards for the evaluation of such discomfort. Therefore, in this study, the suitability of existing vibration comfort-evaluation methods under strong wind conditions was investigated by a full-scale test, and the characteristics of the car-body vibration and momentary discomfort under strong wind conditions were analyzed. It was indicated that low-frequency transient roll motion and transverse motion of the car-body are the main causes of discomfort, and the comfort-assessment methods in European standard (EN-12299) could not be directly used under these conditions. Consequently, an evaluation method for momentary discomfort caused by high-speed trains passing through complex terrain sections under strong wind conditions is suggested.